PEMERTAHANAN BUDAYA LOKAL ACEH PADA PEMBELAJARAN VOKAL GRUP BERBASIS MEDIA VIDEO - Yeni Zuryaningsih; Yuli Astuti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Problems of learning often happen, especially when implementing it in class. The problem in spesific is lack of learning time for practical material in arts and culture-based subjects. This makes the skills that students have cannot be identified and perceived well by the teachers. Students are required to be able to understand theoretical material and practice their abilities as psychomotor values ​​within 3 hours of lessons. The amount of time was too short to sharpen their skills. So video media-based group vocals are a solution that is able to overcome obstacles that occur in the learning process during the co-19 pandemic. This research was conducted using the experimental method type One – Shoot Case Study) in class IX SMP, the test results were analyzed by the t-test and the percentage illustrated in the form of a pie chart. The process of compiling these learning media is able to help students understand the material provided, re-study the material while at home, and sharpen their skills with their colleagues. The material was prepared by involving the local cultures of Aceh for students of Javanese, Batak and Chinese ethnicity via online, it proves that students are more creative and innovative, not only able to sing in a vocal group but also dance and performing theater talents in one group task as well, so that the covid-19 pandemic 19 does not hinder students’ learning process.